Implementasi Pendekatan Realistik Dalam Meningkatkan Pemahaman Siswa Terhadap Luas Bangun Datar Persegi dan Persegi Panjang - Torang Siregar (Universitas Gara Nusantara Padangsidimpuan, 2023)
This research originates from the reality on the ground, for students' academic grades on the subject of geometry, especially the area of flat shapes, is very low. After being identified, it turned out that the students really did not understand the questions, including the working procedures. This can be seen when students are given different questions. This situation is caused because students do not understand the basic concept of the area of a flat shape that is specific to squares and rectangles. This research is an effort to overcome the problems mentioned above, namely to increase students' understanding of the broad concept of flat shapes. a class action research conducted on third grade students at a public elementary school, to be precise Class A at SDN 321 Sinunukan involving 36 students. the principles of classroom action research (CAR) are used to understand the concept of the area of square and rectangular shapes. In their learning students carry out various activities in exploring the surrounding environment which in the end students find their own area of square and rectangular shapes (realistic mathematical approach) so that students are expected to be able to work on questions related to areadepth as a result of students really understand the concept of the area of a square and rectangle.In their learning activities students are assisted by a teaching tool (Mathematics tools) in the form of transparent plastic paper to help students measure the area of an area. in each cycle it is carried out through a series of processes in the form of plans (planning), act/do (action), observation (observation) and reflection (reflection)